2014
DOI: 10.1089/aid.2013.0185
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Function Restoration with Lopinavir/Ritonavir Versus Efavirenz Containing Regimens in HIV-Infected Patients: A Randomized Clinical Trial

Abstract: CD4+ count increase has been reported to be different with lopinavir/r (LPV/r) and efavirenz (EFV)-containing regimens. The different effect of these two regimens on other immune function parameters and the relationship with the gain of CD4 + count have not been assessed in a randomized clinical trial. Fifty antiretroviral treatment (cART) naïve HIV-infected individuals were randomized to receive LPV/r or EFV both with tenofovir/emtricitabine for 48 weeks. A substudy of immunological function restoration was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Previous studies of lymphoid tissue fibrosis have demonstrated no effect of ART but have only evaluated up to 1 year of treatment [37,44,45]. Thus, fibrosis may be stable early after starting ART, but continued suppressive ART may eventually permit resumption of wound healing processes and modest fibrosis reversal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of lymphoid tissue fibrosis have demonstrated no effect of ART but have only evaluated up to 1 year of treatment [37,44,45]. Thus, fibrosis may be stable early after starting ART, but continued suppressive ART may eventually permit resumption of wound healing processes and modest fibrosis reversal.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the participants in this Ghana study were on Tenofovir , Lamivudine , and Efavirenz combination therapy. A study conducted in Barcelona, Spain, indicated that a combination regimen boosted the CD4 count and reduces viral load of participants [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that clinically important CD4+ T lymphocyte count responses are likely to be better defined in terms of absolute postcART CD4+ T lymphocyte counts, rather than change from baseline [ 36 ]. In addition, we have recently reported that differences in CD4+ T lymphocyte gain with different cART regimen are not immunologically meaningful [ 37 ]. Moreover, we have repeated the analysis controlling by time of known HIV infection and CD4+ T lymphocyte count previous to cART and the results were confirmed.…”
Section: Discussionmentioning
confidence: 99%